NATIONAL IDENTITY AND LINGUISTICAL ANALYSIS OF TRANSLATION OF ART TERMS IN UZBEK LANGUAGE - Hojiyeva, Gulchehra (The journal of contemporary issues in business and government, 2021)
This article discusses the origins of terminology and its place in world linguistics. Research by foreign and Uzbek scholars in the field of terminology, as well as the lexical- semantic and national-cultural features of art terms in French and Uzbek languages are also discussed.